2002
DOI: 10.1038/sj.jhh.1001361
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two nimodipine formulations in healthy volunteers

Abstract: The objective of this study was to assess the pharmacokientic parameters of regular nimodipine (Bayer  ), 30 mg, given every 6 h and nimodipine AP (nimodipine in micro particles with programmed action contained in tablets, developed by Biocontrolled-Leti Group Laboratories), 120 mg, given every 24 h. Subjects (19 healthy volunteers, five female; 14 male: age: 21 ± 0.7 years) received one formulation over 5 days. Then, after a washout period of 7 days, the other formulation was given. The analyst was blinded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Nimodipine is a calcium channel blocker used in the treatment of hypertension and stroke. Clinical studies demonstrate a low bioavailability of 4–13% for oral nimodipine [ 92 ]. Nimodipine-loaded SLNs were prepared with palmitic acid, poloxamer 188, and soy lecithin [ 93 ].…”
Section: Oral Delivery Of Slns For Treating Various Diseasesmentioning
confidence: 99%
“…Nimodipine is a calcium channel blocker used in the treatment of hypertension and stroke. Clinical studies demonstrate a low bioavailability of 4–13% for oral nimodipine [ 92 ]. Nimodipine-loaded SLNs were prepared with palmitic acid, poloxamer 188, and soy lecithin [ 93 ].…”
Section: Oral Delivery Of Slns For Treating Various Diseasesmentioning
confidence: 99%
“…Venous blood samples were obtained from all the volunteers pre-drug and 1 h after consumption of each tablet on days 1, 3 and 5 to estimate the serum nimodipine concentration. Nimodipine plasma concentration were analyzed by high performance liquid chromatography following the method of the Quin and Gallo [22,58] with two pumps with Diode array detector and programme class LC10. (Stationary phase: C8 250 9 4.6 mm, particle size 5 lm (nucleosyl/100, C8), volume of injection: 100 ml (automatic).…”
Section: Oral Nimodipine Studymentioning
confidence: 99%
“…(Yan, Ding, Liu, 1993;Lian-Quing, Heng-Shan, Gang, 1993;Dollery, 1999;Blardi et al, 2002;Qiu et al, 2004;Zhonggui et al, 2004;Hernandez-Hernandez et al, 2002). Previous studies showed these data, but sampling was concluded between 5 and 10h after dosing, thereby possibly missing a longer elimination phase.…”
Section: Pharmacokinetic Studymentioning
confidence: 99%